Compaction, aeration and addition of mycotoxin contaminated silage alters the fermentation profile, mycotoxin content and aerobic stability of ryegrass (Lolium perenne) silage - Snelling, Timothy J.; Davies, David R.; Huntington, James A.; Adams, Nick; Warren, Helen; Taylor-Pickard, Jules; Sinclair, Liam A. (Frontiers in Agronomy, 2023)
This study investigated the effect of compaction, aeration and addition of a naturally mycotoxin contaminated ryegrass silage (MCS) containing 1803 µg/kg DM penicillic acid, on the nutritional value and mycotoxin content after ensiling and subsequent aerobic stability of ryegrass Lolium perenne silage (second-cut, June 2020, UK). Mini silos (30 L) were filled with differential compaction (500 kg FW/m3 and 333 kg FW/m3), aeration by injection of air (1L per 48h for 30d then 1L per 7d) and addition of MCS (1.5 g/kg FW ensiled forage) in a 2 x 2 x 2 factorial design. During ensilage, mean CO2% (kg FW) in the aerated silos increased with low compaction. Crude protein (CP) increased and ash decreased with aeration. Mean silage fermentation end products acetic (AA), lactic (LA) and propionic acid (PA) concentrations increased with MCS. PA concentration increased with aeration/low compaction. LA decreased and ethanol increased with low compaction. Mycotoxin profiles differed between the silage on opening and after 14-days incubation in aerobic conditions with disappearance of fusarenon X and penicillic acid and appearance of mycophenolic acid and roquefortine C (317.8 µg/kg DM and 889.6 µg/kg DM). Addition of MCS, increased concentration of penicillic acid on opening with an interaction with aeration (80.58 µg/kg DM MCS x aerated, 40.03 µg/kg DM in the MCS x sealed). Aerobic stability was affected by aeration and low compaction with reduced time taken to heat to +5°C and +10°C above ambient temperature, higher rate of increase in pH and higher cumulative temperatures to the first peak temperature. Higher mycotoxin concentration had a similar effect increasing time to heat +5°C and +10°C above ambient temperatures in aerobic conditions. Regression analysis showed predominantly direct relationships between silage fermentation end-product concentrations and aerobic stability. This study revealed interactions between silage bacteria and fungi activity from the concentrations of fermentation end-products and mycotoxins during ensilage and subsequent aerobic spoilage. The results supported current best practice for silage making, promoting conditions for improved preservation and aerobic stability. The addition of MCS had unexpected positive effects. However, factors associated with the MCS benefiting aerobic stability were not determined.